Front Plow for Smooth, Furrowless Plowing Equipped with Angle Marks (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the proposed technology, with the help of frontal plug bodies, the upper left and right edges of the overturned slabs are first cut with the help of an angle cutter, so that the difficulties in the process of overturning are eliminated and the resistance to traction is reduced. The developed angular plow frontal plow is designed for 4-5 class tractors, its working speed is 6,5-8,5 km/h, coverage width is 2,1 m and processing depth is 25 cm. The angled frontal plow, developed on the basis of theoretical and experimental studies, reliably performed the specified technological work process, and its performance fully corresponds to the agrotechnical requirements and the technical assignment.